Comparing mechanical and enzymatic isolation procedures to isolate adipose‐derived stromal vascular fraction: A systematic review - Uguten, Mustafa; Sluis, Nanouk; Vriend, Linda; Coert, J. H.; Harmsen, Martin C.; Lei, Berend; Dongen, Joris A. (Wound repair and regeneration, 2024)
The stromal vascular fraction of adipose tissue has gained popularity as regenerative therapy for tissue repair. Both enzymatic and mechanical intraoperative SVF isolation procedures exist. To date, the quest for the preferred isolation procedure persists, due to the absence of standardised yield measurements and a defined clinical threshold. This systematic review is an update of the systematic review published in 2018, where guidelines were proposed to improve and standardise SVF isolation procedures. An elaborate data search in MEDLINE (PubMed), EMBASE (Ovid) and the Cochrane Central Register of Controlled Trials was conducted from September 2016 to date. A total of 26 full‐text articles met inclusion criteria, evaluating 33 isolation procedures (11 enzymatic and 22 mechanical). In general, enzymatic and mechanical SVF isolation procedures yield comparable outcomes concerning cell yield (2.3–18.0 × 105 resp. 0.03–26.7 × 105 cells/ml), and cell viability (70%–99% resp. 46%–97.5%), while mechanical procedures are less time consuming (8–20 min vs. 50–210 min) and cost‐efficient. However, as most studies used poorly validated outcome measures on SVF characterisation, it still remains unclear which intraoperative SVF isolation method is preferred. Future studies are recommended to implement standardised guidelines to standardise methods and improve comparability between studies.